Highly Stable Red-Emissive Ratiometric Probe for Monitoring β-Galactosidase Activity Using Fluorescence Microscopy and Flow Cytometry - Lee, Hyo Won; Juvekar, Vinayak; Lee, Dong Joon; Kim, Sun Mi; Kim, Hwan Myung (Analytical Chemistry, 2021)
β-Galactosidase (β-gal), well known as a useful reporter enzyme, is a potent biomarker for various diseases such as colorectal and ovarian cancers. We have developed a highly stable red-emissive ratiometric fluorescent probe (CCGal) for quantitatively monitoring the β-gal enzyme activity in live cells and tissues. This ratiometric probe showed a fast emission color change (620-662 nm) in response to β-gal selectively, which was accompanied by high enzyme reaction efficacy, cell-staining ability, and outstanding stability with minimized cytotoxicity. Confocal fluorescence microscopy ratiometric images, combined with fluorescence-activated cell sorting flow cytometry, demonstrated that CCGal1 could provide useful information for the diagnosis, prognosis, and treatment of β-gal enzyme activity-related diseases such as colorectal and ovarian cancers. Further, it may yield meaningful strategies for designing and modifying multifunctional bioprobes with different biomedical applications.
Keywords: Enzymes activity; Fluorescent probes; Highly stables; Live cell; Live tissue; Ovarian cancers; Ratiometric; Red emissive; Reporter enzymes; β- Galactosidase